DOMESTIC CULTURE SHOCK:A PHENOMENOLOGICAL STUDY OF THE EXPERIENCES OF STUDENTS PARTICIPATING IN A STUDENTS EXCHANGE PROGRAM IN SEMARANG - Srirahayu, Srirahayu; Maulina, Maulina; Syarif, Andi Rachmawati (Universitas PGRI Semarang, 2025)
This study aims to explore the dynamics of adaptation among students participating in the Pertukaran Mahasiswa Merdeka (PMM) Program in Semarang, particularly in the Modul Nusantara activities. Using a qualitative approach with a phenomenological method, this study involved three participants who were interviewed using a semi-structured approach, then analyzed using thematic analysis. The results of the study indicate that the adaptation process of students follows the stages of Lysgaard's model (1955), namely honeymoon, crisis, recovery, and adjustment. In the initial stage, students prepare administratively, mentally, physically, and financially, and build expectations about the new culture. The honeymoon phase is characterized by enthusiasm for the local environment and culture, followed by the crisis phase, which brings about culture shock due to differences in language, food, and social norms. Recovery strategies include observation, asking questions, and building relationships with local students. In the final stage, students feel comfortable, consider the destination city as a second home, and appreciate diversity. The Nusantara module is deemed crucial in introducing local culture, fostering nationalism, and promoting tolerance. These findings underscore the role of PMM as an effective cross-cultural learning tool in the domestic Indonesian context.